The CJEU’s judgment in CHEZ and indirect discrimination by association: an analysis of progress in combating racial or ethnic discrimination in the European Union - Boçon, Mariana Schafhauser (2019)
Since the entry into force of the Directive 2000/43/EC of 29 June 2000 (implementing the principle of equal treatment between persons irrespective of racial or ethnic origin), Member States have been the subject of reports from the European Commission in 2006 and 2014, from which we can analyze the contributions of the Directive in promoting equality. The obstacles faced in the interpretation of concepts such as direct discrimination, indirect discrimination, and positive actions are worthy of note. In addition, what is also important to highlight is the main ethnic groups that suffer from discriminatory practices, as is the case of individuals belonging to the Roma ethnic group in several countries of the European Union. In this text, the author shows the extent to the CJEU’s judgment CHEZ (C-83/14) is an important milestone for the implementation of the Directive 2000/43/EC, by presenting a new interpretation, namely on the possibility of indirect discrimination by association, as this opens up a new understanding of discrimination situations that can significantly impact the current promotion of equal treatment for all persons in the European Union.